Associations of spontaneous self-affirmation with health care experiences and health information seeking in a national survey of US adults. Issue 3 (3rd March 2016) - Taber, Jennifer M.; Howell, Jennifer L.; Emanuel, Amber S.; Klein, William M.P.; Ferrer, Rebecca A.; Harris, Peter R.
Abstract : Objective : Self-affirming – such as by reflecting on one's strengths and values – reduces defensiveness to threatening information, reduces negative effects of stereotype threat and promotes prosociality. These outcomes may promote physical health, highlighting a need to examine the role of self-affirmation in medical and health contexts. Design : Data were collected as part of the nationally representative, cross-sectional, 2013 Health Information National Trends Survey. Items were completed by 2731 respondents. Main Outcome Measures : Respondents answered questions about spontaneous self-affirmation tendencies, perceptions of providers and health care, involvement in medical appointments, health information seeking and engagement in medical research. Results : Spontaneous self-affirmation was associated with more positive perceptions of communication with one's provider, better perceived quality of care, greater likelihood of asking questions in a medical appointment, greater information seeking for oneself and multiple indices of surrogate information seeking (i.e. seeking information for others). Four of eight significant associations remained significant when controlling for optimism. The associations of self-affirmation with aspects of the patient–provider relationship were not modified by factors likely to be associated with stereotype threat (e.g. race or BMI). Conclusion : Spontaneous self-affirmation was related to positive outcomes in health contexts. Experimental research is needed to further explore the causal nature of these associations.